iqbal Pengaruh pelatihan dan motivasi kerja terhadap kinerja karyawan di Koperasi Syariah Benteng Mikro di area 9 - Iqbal, Iqbal; Sutomo; Suhartono (Universitas Tangerang Raya, 2024)
This research aims to determine the effect of training and work motivation, both partial and simultaneous, on employee performance at the Benteng Micro Indonesia Sharia Cooperative Area 9. This type of research uses quantitative methods. This research data was obtained from distributing questionnaires to 70 respondents at the Benteng Micro Indonesia Sharia Cooperative Area 9. The results show that the training variable (X1) has a positive influence on employee performance (Y), the work motivation variable has a positive influence on employee performance (Y). The training variable (X1) and motivation variable (X2) simultaneously influence employee performance (Y). Through the t test (partial) with the calculated t-value of the training variable is 8.126> t-table 1.996 and the significance value is 0.000<0.005. Through the f test (simultaneous) with an F-Calculated value of 639.958 > F-Table 3.13 and a significance value of 0.000 <0.005.